Experience of social mobility and support for redistribution: Accepting or blaming the system? - Nina Weber (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2023)
Using cross-country survey data and a survey experiment, I examine the effects of experienced social mobility on support for redistribution. In line with the self-serving bias, those with negative mobility experiences 'blame the system' and extrapolate from their experience onto society, which increases their demand for redistribution. Conversely, those who experienced positive mobility accept the system and do not extrapolate from their experience onto society, leading to no less support for redistribution. This suggests a potential demand-side explanation for the Great Gatsby Curve: As overall absolute mobility decreases (increases), ceteris paribus, demand for redistribution also decreases (increases).
Keywords: D31; D91; D63; H24; 330; Social mobility; redistribution; attribution bias; self-serving bias